Plastyczne wypuklenie cienkiej płyty kołowej impulsem ciśnienia - Bednarski, T. (Engineering Transactions, 1969)
This paper is devoted to a theoretical and experimental analysis of the plastic curvature creation process of a thin circular plate clamped along its edge and loaded by a pressure impulse applied to the surface of the sample and produced by firing an explosive charge in water. The theoretical description of the problem is founded on the membrane theory of shells in the case of finite strain and a rigid-viscoplastic material. As a result a set of partial differential equations are obtained with the relevent boundary conditions. The experimental part of the work contains a description of the reproduction of the process, the measurement method and the results obtained. The latter concern the distribution of the load displacement strain and strain rate in the course of the straining process of the shell.